Conventional Concepts and New Perspectives for Understanding the Addictive Properties of Inhalants - Jhodie Rubina Duncan; Andrew John Lawrence (Elsevier, 2013)
The abuse of inhaled chemical vapors is a growing problem especially among adolescent populations. This is partly driven by the fact that inhaled products are cheap, accessible, and provide a rapid 'high'. In the brain inhalants have multiple effects. They are neurotoxic, targeting primarily white matter pathways, which is believed to underlie the long-term neurological consequences associated with repeated use. Inhalants are also addictive, resulting in adaptive responses in pathways mediating reward and reinforcement. This includes an ability to alter dopaminergic cell firing and result in long-term mesocorticolimbic dopaminergic dysfunction. However, growing evidence suggests that the reinforcing properties of inhalants may also be driven by their ability to affect neurotransmitter systems other than the dopaminergic system. Both glutamatergic and γ-aminobutyric acid (GABA)ergic systems are emerging as key targets of inhalants with differential responses observed following either acute or chronic exposures. These responses appear particularly important in circuits which appear vulnerable to inhalants and which can also modulate dopaminergic function such as the corticostriatal pathway. Thus in combination with the effects of inhalants on dopaminergic systems, our increased understanding of the role(s) of glutamatergic and GABAergic systems provide new and exciting targets to consider for intervention strategies to limit inhalant use. Keywords:: adolescence, toluene, dopamine, glutamate, GABA